THE INFLUENCE OF PRICES, SERVICE QUALITY, AND FACILITIES ON CUSTOMER SATISFACTION ALFAMART BEKASI BARAT - Ardiprawiro (International Journal Management and Economic, 2024)
This research aims to analyze the influence of price, service quality, and facilities on consumer satisfaction at Alfamart Bekasi Barat. Using quantitative methods, this research involved 100 respondents selected from consumers who had shopped at Alfamart Bekasi Barat. Data was collected through a questionnaire, which included the variables of price, service quality, and facilities, as well as consumer satisfaction. The research results show that price has a positive influence on consumer satisfaction, where affordable prices in accordance with product quality increase satisfaction. Service quality also has a significant effect on consumer satisfaction, with staff friendliness and service conformity to expectations being the main factors. Apart from that, adequate facilities, such as store cleanliness and an organized layout, also contribute to consumer satisfaction. Multiple linear regression analyses reveal that price, service quality, and facilities simultaneously influence consumer satisfaction. This independent variable has a strong relationship with consumer satisfaction, showing the importance of paying attention to these three aspects in modern retail business strategy.